2006
DOI: 10.2215/cjn.00380705
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic Syndrome after Hematopoietic Cell Transplantation

Abstract: Glomerular disease associated with nephrotic syndrome has rarely been recognized as a distinct complication of allogeneic hematopoietic cell transplantation. Case reports in the English and Japanese literature since 1988 have described variable glomerular histology, comprising mainly membranous glomerulonephritis (MGN) in almost two thirds and minimal change disease (MCD) in nearly one quarter of patients. Review of the literature reveals a close temporal relationship between the development of nephrotic syndr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
134
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 54 publications
10
134
1
Order By: Relevance
“…8,11,14,16,18,39,45 We encountered focal segmental glomerulosclerosis in 3 of 14 (21%, patient nos. 6-8) patients with renal biopsy.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8,11,14,16,18,39,45 We encountered focal segmental glomerulosclerosis in 3 of 14 (21%, patient nos. 6-8) patients with renal biopsy.…”
Section: Discussionmentioning
confidence: 89%
“…[7][8][9] Numerous descriptive studies, derived from groups of kidney core biopsy specimens from hematopoietic cell transplant recipients with renal dysfunction, have characterized the most common types of glomerulonephritis in hematopoietic cell transplant patients. 8,[10][11][12][13][14][15][16][17][18] These include membranous nephropathy, minimal change disease, and focal segmental glomerulosclerosis. In addition, acute and chronic thrombotic microangiopathy, or 'transplant-associated thrombotic microangiopathy,' has been shown to occur commonly in hematopoietic cell transplant recipients, 8,14,[17][18][19][20][21][22][23][24][25] with smaller reported numbers of membranoproliferative glomerulonephritis, proliferative glomerulonephritis, ANCA-associated glomerulonephritis, and IgA nephropathy.…”
mentioning
confidence: 99%
“…[1][2][3] In the acute setting, renal failure may be due to renal toxicity of medications (chemotherapeutic, antibiotic, or immunosuppressive), tumor lysis syndrome, renal ischemia (including hypovolemia, veno-occlusive disease, etc), sepsis, infection (bacterial, fungal, or viral), or effects of radiation. [4][5][6] A hemolytic-uremia-like syndrome, often referred to as bone marrow transplant nephropathy, may manifest later (3-6 months or post-transplantation later), and classically shows histopathologic features of thrombotic microangiopathy with endothelial injury. [4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency.…”
mentioning
confidence: 99%
“…[4][5][6] A hemolytic-uremia-like syndrome, often referred to as bone marrow transplant nephropathy, may manifest later (3-6 months or post-transplantation later), and classically shows histopathologic features of thrombotic microangiopathy with endothelial injury. [4][5][6][7] Although exposure of kidneys to radiation during hematopoietic cell transplantation has been hypothesized as a risk factor for bone marrow transplant nephropathy, studies have shown conflicting data regarding renal shielding and long-term renal insufficiency. 5,[8][9][10][11][12] Other causes of thrombotic microangiopathy must be considered in hematopoietic cell transplant recipients, including exacerbation of endothelial injury by chemotherapy, immune-mediated injury, and perhaps most notably, cyclosporine inhibitor toxicity, given as prophylaxis or treatment for graft-versus-host disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation